(untitled) (Research, Society and Development, 2022)
This study aims to understand from the perspective of the nursing team about care of women who suffer pregnancy loss and to identify how integrality is inserted in this context. Descriptive, cross-sectional study with a qualitative approach, carried out with 18 nursing professionals from a reference hospital in Rio de Janeiro – RJ, through an instrument containing subjective questions about knowledge, interpretations and practices in comprehensive care and its approach to women who have suffered loss gestational. Data analyzed using Content Analysis. The content from the interviews could be divided into four axes of categories: The meaning of pregnancy loss in the context oof care; The search for the completeness of the look in the integral care of the woman: Weaknesses in providing comprehensive care to women who suffer pregnancy loss and Potentialities experienced in the management of care for women who suffer the loss. After the analysis, it was possible to conceive that the nursing team is aware of issues related to comprehensive care for women who experience pregnancy loss. The categories reinforce the significance of the theme, showing that despite the difficulties, the hospital environment of the maternity hospital is a propitious, strategic and essential place for the continuity of full care within the Health Care Network od the Unificed Health System.